Values of Outdoor Fitness Facilities for Urban Senior Citizens: A Case Study of Bangkok: คุณค่าของเครื่องออกกำลังกายกลางแจ้งสำหรับผู้สูงอายุในเมือง: กรณีศึกษากรุงเทพมหานคร - Bejranonda, Somskaow (Journal of Applied Economics and Management Strategy, 2019)
บทคัดย่อ งานวิจัยนี้ต้องการศึกษาความต้องการด้านนันทนาการและการออกกำลังกายของผู้สูงอายุ และคุณค่าของเครื่องออกกำลังกายกลางแจ้งสำหรับผู้สูงอายุในกรุงเทพมหานคร เพื่อชี้ให้เห็นถึงประโยชน์ในการจัดหาเครื่องออกกำลังกายกลางแจ้งให้กับประชาชนโดยเฉพาะผู้สูงอายุในเมือง อันจะเป็นการเสริมสร้างสุขภาพกายและใจของผู้สูงอายุซึ่งจะช่วยให้เมืองประหยัดงบประมาณในการดูแลรักษาพยาบาลผู้สูงอายุที่จะมีจำนวนเพิ่มมากขึ้น โดยใช้วิธีการประเมินมูลค่าทางเศรษฐศาสตร์ที่เรียกว่า Contingent Valuation Method (CVM) ซึ่งได้จากการสอบถามกลุ่มตัวอย่างผู้สูงอายุจำนวน 601 คน ในปี พ.ศ. 2560 พบว่า ประโยชน์หรือคุณค่าของเครื่องออกกำลังกายที่มีต่อผู้สูงอายุนั้นคิดเป็นมูลค่าประมาณ 172 บาท/คน/ปี และเมื่อคิดเป็นมูลค่ารวมทั้งสิ้นประมาณ 169.5 ล้านบาท/ปี โดยผู้สูงอายุต้องการให้กรุงเทพมหานครจัดให้มีอุปกรณ์ที่เหมาะสมในการออกกำลังกายของผู้สูงอายุบริเวณพื้นที่สาธารณะ รวมทั้งจัดให้มีกิจกรรมการออกกำลังกายที่เหมาะสมกับผู้สูงอายุ และจัดเจ้าหน้าที่ที่มีความรู้เกี่ยวกับการออกกำลังกายเพื่อแนะนำผู้สูงอายุ คำสำคัญ: ผู้สูงอายุในเมือง เครื่องออกกำลังกายกลางแจ้ง วิธีการสมมติเหตุการณ์ให้ประมาณค่า ABSTRACT This study aimed to explore the demand of urban senior citizens for recreation and exercise, and to investigate the values of outdoor fitness facilities for senior citizens in Bangkok. These values will reflect the benefits of using outdoor fitness facilities by urban senior citizens, which will help the city save money in caring for the elderly, whose numbers will increase steadily due to the strengthening of the physical and mental health of senior citizens. Under the Contingent Valuation Method (CVM), data were collected from 601 respondents in 2017, and the results showed that the value or the benefits of using outdoor fitness facilities for senior citizens was worth THB 172/person/year. The total value was THB 169.5 million. Further, the demand analysis revealed that most respondents would like the Bangkok Metropolitan Administration (BMA) to provide appropriate outdoor fitness facilities and activities for senior citizens in public areas, and arrange staffs with knowledge about exercising that can be introduced to senior citizens. Keywords: Urban Senior Citizens, Outdoor Fitness Facilities, Contingent Valuation Method (CVM)